Seguimiento farmacoterapéutico en pacientes con cefalea vascular y cefalea postraumática crónica atendidos en un hospital de Iquitos, 2023 - Alvan Malafaya, Klancy Maykeyko (2024)
Once the research work was carried out and considering the objectives of identifying the sociodemographic characteristics, identifying a problem related to medications and evaluating, through pharmacotherapeutic monitoring, the intensity of pain in patients with vascular headache and chronic post-traumatic headache, who are treated in the office of neurosurgery at Hospital III- Iquitos, EsSalud, during the months of January to September 2023. The methodology carried out was quantitative, observational, prospective, descriptive and transversal design; The most important results were: Problem related to medications PRM4 with 42.3% in vascular headache and PRM 4, 5, 6, with 10.0% in post-traumatic headache, the visual analogue evaluation of the initial pain (VAS1) had intense pain of 90.6% and after pharmacotherapeutic follow-up to moderate pain (VAS2) with 78.8% for vascular headache and in post-traumatic moderate pain (VAS1) of 70.0% and after pharmacotherapeutic follow-up to mild pain with 55.0% . It is concluded that pharmacotherapeutic monitoring allowed a decrease in pain intensity in patients with vascular and post-traumatic headaches treated at Hospital III-Iquitos, EsSalud, during the year 2023.